The challenges for Croatian fisheries within current regulatory environment - Runko Luttenberger, Lidija (Array, 2021)
Biodiversity as a planetary boundary and sustainability are strongly related to fish stocks and fisheries that are regulated by a number of sources of law with the aim of achieving their sustainability. The paper analyses current application, impact and effectiveness of the Common Fisheries Policy that sets the rules for fishing fleets management in the European Union and for fish stocks conservation as well as the 2020 Report on its implementation by the European Court of Auditors. It also examines the present and potential implementation and effects of Blue Growth, Marine Strategy Framework Directive, United Nations legal framework and Sustainable Development Goals on fisheries and aquaculture activities in the Adriatic Sea, a semi-enclosed and biodiversity rich sea. Improvements in implementing marine ecosystem approach and marine spatial planning are proposed in policy and regulatory framework, focusing on characteristics of the Adriatic Sea. Resilient solutions require placing more focus on characteristics of regional seas and applying site-specific tailor-made solutions and less complex but efficient governance for the seas which entail integrated approach to exploitation and preservation of the resources and their health.